2010
DOI: 10.1007/s12639-010-0006-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug targets in Leishmania

Abstract: Leishmaniasis is a major public health problem and till date there are no effective vaccines available. The control strategy relies solely on chemotherapy of the infected people. However, the present repertoire of drugs is limited and increasing resistance towards them has posed a major concern. The first step in drug discovery is to identify a suitable drug target. The genome sequences of Leishmania major and Leishmania infantum has revealed immense amount of information and has given the opportunity to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
128
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 94 publications
(77 reference statements)
0
128
0
1
Order By: Relevance
“…Therefore, the development of alternative drugs for the treatment of the different clinical forms of leishmaniasis is a priority for controlling the disease (Croft et al 2006;Castillo et al 2010). Great efforts have been made to identify potential chemotherapeutic targets in the genome and proteome of Leishmania sp., in the hope of devising more effective treatments (Myler 2008;Concu et al 2009;Chawla and Madhubala 2010). Proteolytic enzymes or proteinases play an essential role in the parasite's survival.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of alternative drugs for the treatment of the different clinical forms of leishmaniasis is a priority for controlling the disease (Croft et al 2006;Castillo et al 2010). Great efforts have been made to identify potential chemotherapeutic targets in the genome and proteome of Leishmania sp., in the hope of devising more effective treatments (Myler 2008;Concu et al 2009;Chawla and Madhubala 2010). Proteolytic enzymes or proteinases play an essential role in the parasite's survival.…”
Section: Introductionmentioning
confidence: 99%
“…The first step in drug discovery is to identify a suitable drug target that should be necessary for the survival of the pathogen and should be either absent from the host or substantially different from the host homolog (23). The intracellular pathogen Leishmania exhibits a strong antioxidant defense mechanism by using hemoproteins such as APx of the glutathione-ascorbate cycle for its survival and replication against the oxidants (H 2 O 2 ) released by the macrophage under oxidative burst conditions (10).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, topoisomerase inhibitors or poisons have been shown to have activity against trypanosomatid protozoa, mediating apoptosis-like death (Smirlis et al 2010 ). Moreover, the antileishmanial compounds sodium stibogluconate and urea stibamine have been shown to act via the inhibition of type I topoisomerase (Chawla and Madhubala 2010 ). Camptothecin, a drug that acts as a poison against leishmanial topoisomerase I ( Das et al 2006a ), has been found to block L .…”
Section: Topoisomerasesmentioning
confidence: 99%